Psychometric characteristics of the FertiQoL questionnaire in a German sample of infertile individuals and couples - Sexty, Réka E.; Lallinger, Mariana; Rösner, Sabine; Strowitzki, Thomas; Wischmann, Tewes (Health and quality of life outcomes, 2018)
FertiQoL is a questionnaire internationally developed to measure fertility-specific quality of life. It has been validated with infertile populations in many countries and used in several studies focusing on the psychosocial consequences of infertility in Europe, Asia, and North America.